EFFECTIVENESS OF CERVICAL LAMINOFORAMINOTOMY FOR UNILATERAL SOFT DISC HERNIATION - Ali, Asghar; Khan, Shahbaz Ali; Khan, Ehtisham Ahmed; Hussain, Abid; Aurangzeb, Ahsan; Javed, Fatima; Khattak, Haider Ali; Qazi, Amir Hamza (Journal of Ayub Medical College Abbottabad, 2025)
Background: Cervical disc herniation is one of the very few morbid and prevalent spinal conditions affecting quality of life, often leading to debilitating symptoms. Early recognition of signs and symptoms is crucial for timely intervention, as conservative methods may prove insufficient in cases with neurological deficits. Surgical interventions, including anterior and posterior approaches, as well as hybrid approaches, have evolved to address the challenges posed by cervical disc herniation and cervical spondylosis. This study explores the effectiveness of laminoforaminotomy, a targeted surgical approach for unilateral soft disc herniation. The technique aims to achieve optimal clinical outcomes by minimizing disruption to adjacent tissues and preserving motion segments. Methods: A retrospective study was conducted on 23 patients diagnosed with cervical radiculopathy who underwent posterior keyhole laminoforaminotomy between February and July 2023 at a Tertiary Care Hospital in Peshawar, Results: The age distribution of the participants ranged from 32 to 67 years, with the largest group in the 41‒50 age range. Males constituted 69.56% of the patients. The distribution of cervical disc herniations varied across levels, with the C4-C5 level exhibiting the highest occurrence. Postoperative complications were observed in 3 out of 23 patients, resulting in an 82.62% success rate. Conclusion: Laminoforaminotomy demonstrates promising short-term results in addressing unilateral soft disc herniation, with an 82.62% success rate.